2020
DOI: 10.1186/s12876-020-01230-1
|View full text |Cite
|
Sign up to set email alerts
|

Causative factors of liver fibrosis in HIV-infected patients. A single center study

Abstract: Background Liver disease is a leading cause of morbidity and mortality among Human Immunodeficiency virus (HIV) infected patients; however no consensus exists on HIV-related risk factors for it. The aim of this study was to identify risk factors for liver fibrosis/cirrhosis in a cohort of Greek HIV-infected patients. Methods Patients attending the HIV outpatient clinic of Pathophysiology Department at «Laiko» General Hospital in Athens, Greece, between December 2014 and December 2017 were eligible for inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
1
13
1
Order By: Relevance
“…Several studies have confirmed the possible causes contributing to the progression of liver fibrosis in PLWH, in particular, age, coinfections with viral hepatitis and alcohol abuse [ 19 , 20 , 21 , 22 , 23 , 24 ]. On the other hand, the potential effect of body mass index and the presence of hypertriglyceridemia or diabetes mellitus are debated and inconclusive [ 22 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed the possible causes contributing to the progression of liver fibrosis in PLWH, in particular, age, coinfections with viral hepatitis and alcohol abuse [ 19 , 20 , 21 , 22 , 23 , 24 ]. On the other hand, the potential effect of body mass index and the presence of hypertriglyceridemia or diabetes mellitus are debated and inconclusive [ 22 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human immunodeficiency virus-induced immunosuppression has been shown to affect levels of qAnti-HBc, but not particularly qHBcrAg [ 32 ], and longer periods of HIV infection have been associated with higher degrees of biopsy-assessed liver fibrosis [ 33 ], both of which could have affected the association between these markers and fibrosis. Human immunodeficiency virus virological and immunological variables did not borne out as determinants for transitions between liver fibrosis states, with the exception of CD4 + /CD8 + ratio during follow-up and liver fibrosis regression (HR = 2.90; 95% CI, 1.41–5.97), which has been associated with liver fibrosis levels in HIV infection [ 25 , 26 ] and was adjusted for in our model. Other confounding variables include ART-related hepatotoxicity and metabolic hepatic manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…The hazard ratios (HRs) comparing TI per unit increase in marker levels at baseline, during follow-up and change between visits, were estimated with proportional hazards of the TI. Multivariable adjustment was made using predefined covariates from a previous study in TDF-treated coinfected patients: age, gender, duration of ART, and protease inhibitor (PI)-containing ART [ 7 ], as well as CD4 + /CD8 + ratio during follow-up [ 25 , 26 ]. Model fit was assessed by plotting the observed and expected prevalence of belonging to a given fibrosis group [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Apart from those already mentioned, other factors associated with significant LF appear to be chronically elevated serum alanine aminotransferase (ALT) and gamma glutamyl-aminotransferase (γGT) levels, while findings concerning body-mass index and the presence of hypertriglyceridemia or diabetes mellitus (common predisposing factors for NAFLD) are inconsistent [ 26 , 28 , 30 , 32 , 33 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Liver Fibrosis In Hiv-infected Individualsmentioning
confidence: 99%
“…Several studies have explored the possible causes of liver fibrosis in HIV-infected patients, with most of them pointing out viral hepatitis co-infections, age, and alcohol abuse as the major risk factors [ 16 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. On the other hand, the long-term hepatotoxicity of ART has been debated, with various studies remaining inconclusive.…”
Section: Introductionmentioning
confidence: 99%